Impact of skeletal muscle loss during conversion therapy on clinical outcomes in lavage cytology positive patients with gastric cancer - Ding, Ping’an; Yang, Peigang; Yang, Li; Sun, Chenyu; Chen, Shuya; Li, Min; Lowe, Scott; Guo, Honghai; Tian, Yuan; Liu, Yang; Zhao, Qun (Frontiers in Oncology, 2022)
Background The relationship between sarcopenia and clinical outcomes during conversion therapy in patients with lavage cytology positive gastric cancer (GC-CY1) remains unclear. This study aimed to investigate the impact of sarcopenia and skeletal muscle loss on the efficacy of conversion therapy, tumour response and survival in GC-CY1 patients. Methods Retrospective analysis of data from a prospective trial of conversion therapy conducted between April 2018 and August 2019 in patients with GC-CY1 (NCT03718624). Skeletal muscle index (SMI) was measured at the level of the third lumbar (L3) vertebra and the sarcopenia was defined using published cut-off points in all patients. We defined ΔSMI (%)/50 days above 9.53% for men and ΔSMI (%)/50 days above 8.81% for women as significant muscle loss (SML) and analysed the changes in skeletal muscle during conversion therapy in relation to treatment efficacy, survival and tumour response. Results Of the 36 patients, 7 patients (19.44%) developed sarcopenia before conversion therapy, 6 (16.67%) developed new sarcopenia after conversion therapy, and 8 (22.22%) developed SML during treatment. Multivariate analysis showed that sarcopenia before treatment [Odds Ratio (OR) =8.923, 95%CI: 1.341-25.321, p=0.002] and SML during treatment (OR=7.803, 95%CI: 1.106-16.189, p=0.001) had a negative impact on the success rate of conversion therapy. Cox multifactorial analysis found that pre-treatment sarcopenia [overall survival (OS): Hazard Ratio (HR) =6.341, 95%CI: 1.269-18.943, p=0.001; progression-free survival (PFS): HR=8.212, 95%CI: 1.569-36.582, p=0.001], newly developed sarcopenia after conversion therapy (OS: HR=3.189, 95%CI: 1.023-9.811, p=0.012; PFS: HR=3.084, 95%CI: 1.042-14.236, p=0.013) and the presence of SML during treatment (OS: HR=10.234, 95%CI: 2.532-54.231, p=0.002; PFS: HR=9.562, 95%CI: 2.341-38.092, p=0.002) were independent risk factor for OS and PFS in GC-CY1 patients. Conclusion Pre-treatment sarcopenia and the presence of SML during treatment are strongly correlated with the immediate and long-term outcomes of GC-CY1 patients and can be used as imaging markers to predict the treatment efficacy and prognosis of patients in clinical practice.